The clinical spectrum of MELAS and associated disorders across ages: a retrospective cohort study - Cox, Benjamin C.; Pearson, Jennifer Y.; Mandrekar, Jay; Gavrilova, Ralitza H. (Frontiers in Neurology, 2023)
Objective: Mitochondrial encephalomyopathy, lactic acidosis, and stroke-like episodes (MELAS) is a severe multisystemic disease, although some have a milder phenotype. We aimed to evaluate the clinical spectrum of this disease from MELAS patients to asymptomatic carriers and identify predictors of severity.We reviewed 81 patients, who had MELAS or had positive genetics without meeting clinical criteria. Patients who met criteria including lactic acidosis, encephalomyopathy, and stroke-like episodes (SLE) were categorized as MELAS, symptomatic non-MELAS, and asymptomatic. MELAS was further categorized as "standard-onset" if the first stroke-like episode (SLE) occurred before age 40 or "lateonset".Results: Eighty-one patients were included: 42 MELAS (13 late-onset), 30 symptomatic non-MELAS, and 9 asymptomatic. MELAS patients had lower BMI at onset (mean 18.6 vs. 25.1 asymptomatic and 22.0 symptomatic non-MELAS, P<0.05). There was a trend towards higher serum heteroplasmy in MELAS compared to symptomatic non-MELAS and asymptomatic (means 39.3%, 29.3%, and 21.8% P=0.09). Symptomatic non-MELAS had more sensorineural hearing loss as first presenting symptom (51.6% vs. 24.4%, P<0.05). MELAS had higher prevalence of seizures (88.1% vs 16.7%, P<0.05) and shorter survival from onset to death (50% mortality at 25 years vs 10%, P < 0.05).Late-onset MELAS had longer disease duration from first symptom to first SLE (mean 16.6 vs 9.3 yrs.) and also lived longer (mean age at death 62 vs 30). Standard-onset MELAS had more neurologic involvement at onset than late-onset (51.7% vs 15.4%). Late-onset patients had more prevalent diabetes (69.2% vs 13.8%) and nephropathy (53.8% vs 10.3%). Patients with late-onset MELAS also had more organ systems involved (mean 4.1 vs 2.7, P<0.05). There was a trend towards higher heteroplasmy levels in standard-onset (mean 44.8% vs 25.3%, P=0.18).Discussion: Our study highlights the spectrum of MELAS. The lower BMI in MELAS at presentation as well as higher rates of sensorineural hearing loss as initial symptom in symptomatic non-MELAS may be useful clinical markers. While many patients present before age 40 with SLE, some can present with SLE later in life. Standard onset MELAS is more likely to present with neurologic symptoms. Late-onset is more likely to suffer diabetes or nephropathy and have more organ systems involved.